Parentsâ€™ perception on â€œBelajar Dari Rumahâ€ progam for elementary students - Putri, Risna Estuning (CV. Mitra Palupi, 2021)
Background: Â Program â€œBelajar dari Rumahâ€ at TVRI is an alternative distance learning for students, teachers and parents during studying at home as the COVID-19 outbreak.Purpose: This research aims to determine the perceptions or opinions of parents about the program. This research is hopefully can be used as evaluation material to improve and to perfect the program.Design and methods: In its implementation, this research used a case study with an analytical descriptive method that intends to describe the results of the study and tries to find a picture of a situation or phenomenon that is happening. The objects in this study are parents who accompany children during the implementation of distance learning programs. This research reveals a number of parents' perceptions about the the program Belajar dari Rumah on TVRI. This research was conducted in two areas in Lampung Province, Metro City and East Lampung Regency.Results: A number of parents who have watched and accompanied their children during the implementation of distance learning think that the program is far from perfect.